Inventory of Diderot's 'Encyclopédie' - Schwab, R; Rex, W (Voltaire Foundation, 2017)
Acknowledgements Introduction 1. The contents of the inventory 2. Designation of categories 3. Textual problems 4. Problems of attribution 5. The problem of Diderot's articles 6. Other matters of attribution 7. The editorial material in the first eight volumes 8. Ornaments in the text 9. Editions bearing the Paris-Neufchastel imprint 10. Variants in titles and signs of attribution in the first three editions of volumes I-III 11. The Riverside counterfeit volumes I-VII and their relationship with the original editions and the Geneva folio edition 12. Table of variants in the original edition, the Geneva edition, and the Riverside volumes Appendix A. Collation of the Discours préliminaire, the *Explication détaillée du systême des connoissances humaines, and the *Systême figuré des connoissances humaines of Diderot's 1750 prospectus Appendix B. The censored texts and the cancels Appendix C. The article CONSTITUTION UNIGENITUS Appendix D. The censored text of the article GOMARISTES Appendix E. Variants in later editions of the Discours préliminaire, the Avertissement of volume III, and the Eloges of Montesquieu, Mallet, and Dumarsais Appendix F. Variants in Encyclopédie articles republished elsewhere